2012
DOI: 10.1038/ncomms2324
|View full text |Cite
|
Sign up to set email alerts
|

Observations of ubiquitous compressive waves in the Sun’s chromosphere

Abstract: The details of the mechanism(s) responsible for the observed heating and dynamics of the solar atmosphere still remain a mystery. Magnetohydrodynamic waves are thought to have a vital role in this process. Although it has been shown that incompressible waves are ubiquitous in off-limb solar atmospheric observations, their energy cannot be readily dissipated. Here we provide, for the first time, on-disk observation and identification of concurrent magnetohydrodynamic wave modes, both compressible and incompress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
215
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(254 citation statements)
references
References 35 publications
28
215
3
Order By: Relevance
“…In particular the periodic, transverse displacement of magnetic flux tubes in both the chromosphere (De Pontieu et al 2007; Kuridze et al 2012;Morton et al 2012) and in the corona (Tomczyk et al 2007;Erdélyi & Taroyan 2008). The chromospheric motions are somewhat better resolved as they are observed with high-resolution (<0.…”
Section: Introductionmentioning
confidence: 99%
“…In particular the periodic, transverse displacement of magnetic flux tubes in both the chromosphere (De Pontieu et al 2007; Kuridze et al 2012;Morton et al 2012) and in the corona (Tomczyk et al 2007;Erdélyi & Taroyan 2008). The chromospheric motions are somewhat better resolved as they are observed with high-resolution (<0.…”
Section: Introductionmentioning
confidence: 99%
“…Morton et al 2012b), providing the data noise as errors for the fitting. The Gaussian centroid is taken as the central position of the jets axis, and to the associated errors from the fit we add the estimated remaining displacement error.…”
Section: Transverse Oscillations On Jetmentioning
confidence: 99%
“…A&A 578, A60 (2015) In this paper we focus on axisymmetric slow and fast sausage modes, which have recently been discovered in numerous structures, but have not been adequately modelled to estimate their energy content. They have been detected in coronal loops (De Moortel et al 2000;Wang et al 2002Wang et al , 2003Krishna Prasad et al 2012), in photospheric pores (Dorotovič et al 2008(Dorotovič et al , 2014Morton et al 2011;Moreels et al 2015), in network bright points (McAteer et al 2003;Bharti et al 2006;Martínez González et al 2011), in flares (Nakariakov et al 2003;Melnikov et al 2005;Van Doorsselaere et al 2011), and in the chromosphere (Morton et al 2012a). Some authors have attempted to estimate the amount of energy present in these observations.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have attempted to estimate the amount of energy present in these observations. Morton et al (2012a) have observed both sausage and kink modes in the chromosphere and used MHD theory to estimate the energy in the waves. They found that the energy of compressive (sausage) waves was higher than the energy in transverse waves.…”
Section: Introductionmentioning
confidence: 99%